An industrial application study of the GCD design methodology for product oriented manufacturing - Silva, Sílvio Carmo (2003)
This paper presents an application and test study, carried out in a garment company in the Minho region in the North of Portugal, of the Generic - Conceptual-Detailed (GCD) methodology for designing Product Oriented Manufacturing Systems (POMS). The methodology is in an advanced stage of development and is now being submitted to a refining process based on findings from application tests in industry.